Use of β‑blockers and risk of age‑related macular degeneration among hypertensive patients: An insight from The National Health and Nutrition Examination Survey. (2023) - Luo, Yili; Liu, Jianpeng; Feng, Wangqiang; Lin, Da; Song, Guangwei; Chen, Mengji; Zheng, Haihua
No abstract available